Nilai-Nilai Pendidikan Multikultural dalam Mata Pelajaran Aswaja dan ke-NU-an Siswa SMP/MTs - Bukhori, Imam (At- Ta'lim : Jurnal Pendidikan, 2018)
Aswaja and NU's Education taught in Nahdlatul Ulama educational institutions, especially for junior high school / MTs are directed to maintain, preserve, develop and practice Ahlu al-Sunnah Wal Jama'ah Islam teachings and conduct activities aimed at to create the benefit of society, the progress of the nation and the height of human dignity and dignity that can be understood very in tune with the values of multicultural education. The values of multicultural education include: (1) the value of democracy, equity and justice; (2) the value of humanity, togetherness, and peace; and (3) social attitudes, namely: recognition, acceptance and appreciation to others is very appropriate and all of which are covered in Aswaja and NU's educational content for junior high school / MTs, ie al-ta'awun, al-tawasuth, al-i'tidal, al-tasamuh, al-tawazun, and amar ma'ruf nahi munkar, and ukhuwah baikukhuwah nahdliyah, islamiyah, wathaniyah, basyariyah and then embodied in the form of mabadi 'khaira ummat which originated from al-shidqu norm, al -aahah wa al-wafa bi al-'ahdi, al-'adalah, al-ta'awun and al-istiqamah.Hal affirms that the practice of Aswaja and NU's education is taught in educational institutions within the organization Nahdlatul Ulama very inclusive. Internally, education in Nahdlatul Ulama 'organization has been proven to have introduced multicultural values to its students both in terms of doctrine of the teachings, as well as in terms of the daily life experiences of the students. Externally, these multicultural values are also socialized and made into principles in establishing social relationships with communities and other groups outside Nahdlatul Ulama's educational institutions'. Keywords: Values of Multicultural Education, Aswaja Subjects and Nuns, SMP / MTs.